2003
DOI: 10.1080/1042819021000035699
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Chimerism of Bone Marrow Vessels (Endothelial Cells, Myofibroblasts) Following Allogeneic Transplantation for Chronic Myelogenous Leukemia

Abstract: Experimental findings support the hypothesis that within the functional network of the bone marrow (BM) microenvironment the endothelial cells (ECs) exert a pivotal role as gatekeepers by controlling the trafficking and homing of progenitor cells. However, little information is available concerning the origin of ECs after allogeneic bone marrow transplantation (BMT) in CML. To determine the extent of mixed chimerism (MCh) a simultaneous immunohistochemical and fluorescence in-situ hybridization (FISH) study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Two earlier studies, which did not find donor-type endothelial cells in the stromal constituents of bone marrow up to 3 years after HSCT, 29,30 were contrasted by several reports showing endothelial cell chimerism in skin, gut, heart and bone marrow after gender-mismatched HSCT. [14][15][16][17][18]31,32 All these studies used XY in situ hybridization for the detection of donor-derived cells. Reported numbers of donor-type bone marrow-derived endothelial cells after HSCT varied from 2% in non-GVHD-affected skin and gastrointestinal tract up to 40% in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two earlier studies, which did not find donor-type endothelial cells in the stromal constituents of bone marrow up to 3 years after HSCT, 29,30 were contrasted by several reports showing endothelial cell chimerism in skin, gut, heart and bone marrow after gender-mismatched HSCT. [14][15][16][17][18]31,32 All these studies used XY in situ hybridization for the detection of donor-derived cells. Reported numbers of donor-type bone marrow-derived endothelial cells after HSCT varied from 2% in non-GVHD-affected skin and gastrointestinal tract up to 40% in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion donor chimerism has been described in the endothelium of skin, gut, heart and bone marrow in patients after HSCT. [14][15][16] Furthermore, it was recently suggested that donorderived endothelial cells participate in endothelial repair during the effector phase of acute GVHD, 17 and donorderived endothelial cells were detected in 25% of sexmismatched skin biopsies following HSCT, especially in patients with acute GVHD, and at later time points. 18 Among others, ABH histo-blood group antigens expressed on endothelial cells represent a potential target for GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a minimal dose-limiting effect may play a role when it comes to the contribution of transplanted, marrow-derived, true repopulating endothelial progenitors with the capacity to form HPP-ECs (CFU-ECs) [45]. Most of the bone marrow vasculature itself after lethal irradiation and whole bone marrow transplantation is host derived in humans [57] and in mice (H.G. Kopp, unpublished data), regardless of the degree of hematopoietic engraftment.…”
Section: Evidence For the Contribution Of Endothelial Progenitors To mentioning
confidence: 99%
“…In combination with immunohistochemical analysis this assay allows the genotyping of single phenotyped cells. Assuming that in CMPD the source of relapse probably is the undifferentiated hematopoietic progenitor cell FISH analysis also is an important tool in monitoring hematopoietic engraftment in the BM after transplantation (26).…”
Section: Discussionmentioning
confidence: 99%